The oxidation mechanism and kinetics of limononic acid by hydroxyl radical in atmospheric aqueous phase. (1st February 2023) - Chen, Yanqi; Lv, Guochun; Wang, Yan; Li, Xiaofan; Sun, Juan; Zhou, Xuehua; Sun, Xiaomin
Abstract: Limononic acid (3-isopropenyl-6-oxoheptanoic acid, LA), as an important precursor of secondary organic aerosols (SOA), has attracted extensive attention in the field of atmospheric chemistry. However, its microscopic oxidation mechanism is still unclear. In this study, the density functional theory calculations were conducted to study the oxidation mechanism of LA by ·OH in aqueous phase. The results show that the reactions of hydroxylation are more likely to occur than the dehydrogenation reaction, because of the lower free energy barrier (2.3–5.4 kcal mol −1 ). At 298 K, the total rate constant of the reaction initiated by ·OH is 1.06 × 10 10  M −1  s −1, which fits the experimental value well. Among all reactions, the hydroxylation reaction in C9 site of LA is the most favorable pathway, and the corresponding hydroxylation intermediate (IM4) can react with ·OH, H2 O, dissolved O2, and HO2 ·. Three important tropospheric free radicals (R·, RO· and RO2 ·) are generated during the subsequent reaction process. Meanwhile alcohols, ketones, aldehydes, and oxidized acids can be formed in the overall reaction scheme. These products are the precursor for the formation of SOA, and this transformation process will increase the O/C ratio of aqueous phase SOA. This study has an important significance for understanding the oxidation mechanism of monoterpenoids in the atmospheric aqueous phase. Graphical abstract: Image 1 Highlights: OH-addition reaction of C9 site is more like to occur of LA. The intermediate can react with ·OH, H2 O, dissolved O2, and HO2 . Three important tropospheric free radicals (R·, RO· and RO2 ·) are generated during the reaction process. The transformation process will increase the O/C ratio of aqueous phase SOA.